2013
DOI: 10.1002/clen.201200575
|View full text |Cite
|
Sign up to set email alerts
|

Status of Macrobenthic Community and Its Relationships to Trace Metals and Natural Sediment Characteristics

Abstract: Laizhou Bay, located in the northwest of Shandong Peninsula, has complex transitional environments between terrestrial and marine ecosystems. In the present study, a total of 122, 131, and 139 species were collected in spring, summer, and autumn 2011, respectively. Species constitutions of macrobenthos were grouped into four phyla, of which annelida were the most abundant phylum, the average biomass proportion of echinodermata was the lowest, and the proportion of important species for mollusca was the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this study, the observed positive correlation between H' and heavy metals was perplexing, as it is generally expected that higher concentrations of metals typically reduce macrobenthic community diversity [69]. Moreover, the mechanisms by which metal contaminants harm organisms often differ from those associated with organic pollution [70].…”
Section: Discussionmentioning
confidence: 75%
“…In this study, the observed positive correlation between H' and heavy metals was perplexing, as it is generally expected that higher concentrations of metals typically reduce macrobenthic community diversity [69]. Moreover, the mechanisms by which metal contaminants harm organisms often differ from those associated with organic pollution [70].…”
Section: Discussionmentioning
confidence: 75%
“…This ratio has proven especially effective to detect benthic disturbances in response to human pressures resulting from oil spills or offshore oil and gas production (e.g. Gomez and Dauvin, 2000;Nikitik and Robinson, 2003;Andrade and Renaud, 2011;Joydas et al, 2011Joydas et al, , 2012Sukumaran et al, 2013;Seo et al, 2014;Spagnolo et al, 2014), organic enrichment in sediments due to sewage discharge , 2012bVazirizadeh and Arebi, 2011;Subida et al, 2012;Pinedo et al, 2012;Serrano et al, 2014), fish farms (Keeley et al, 2012;Jahani et al, 2012;Karakassis et al, 2013;Zhang et al, 2013;Riera and de-laOssa-Carretero, 2013;Aguado-Giménez et al, 2015), organic and heavy metal contamination and diverse human activities (Dauvin et al, , 2012Munari and Mistri, 2007;Pranovi et al, 2007;Blanchet et al, 2008;Bakalem et al, 2009;Grimes et al, 2010;Pelin, 2011;Wetzel et al, 2012;Caglar and Albayrak, 2012;Saddik and Zourarah, 2013;Taupp and Wetzel, 2013), mosaic of habitats (Bouchet and Sauriau, 2008;Munari and Mistri, 2008;Lavesque et al, 2009;Do et al, 2011Do et al, , 2012Culhane, 2012), eutrophication (Afli et al, 2008;Zhang et al, ...…”
Section: Discussionmentioning
confidence: 99%
“…S. scutata was a deep burrowing depositfeeder and had a low growth rate and a long life span, which was supposed to be the characteristics of pollution tolerant species (Salen-Picard et al, 2003). Although the other two species, G. gurjanovae and E. bilineata, were mentioned in some studies (Jensen and Bender, 1972;Lim et al, 2006;Zhang et al, 2013), their ecological features have not been studied explicitly.…”
Section: Effect Of Contaminationmentioning
confidence: 97%